The synergy of linagliptin and empagliflozin in catering to diabetes mellitus in Pakistan - Ainan Arshad; Kashif Khan; Muhammad Shoaib (Journal of the Pakistan Medical Association, 2025)
Diabetes is rapidly increasing globally, especially in low- and middle-income countries, with Pakistan ranking third in prevalence, having 33 million people. The lack of adherence to the first-line treatment, metformin, mainly due to gastrointestinal side effects, is a significant concern. A novel approach for managing type 2 diabetes in Pakistan is to combine linagliptin and empagliflozin. Linagliptin is well-tolerated and suitable for those who cannot tolerate metformin, while empagliflozin reduces cardiovascular risks and nephropathy, showing promising results in controlling diabetes with minimal side effects. The synergy between linagliptin and empagliflozin could greatly improve diabetes management and patient wellbeing. It is recommended that healthcare providers in Pakistan use social media and seminars to educate the public on this new treatment option to tackle the diabetes crisis effectively. Key Words: Diabetes, Linagliptin, Empagliflozin, Combination therapy, Pakistan.